Unruptured arteriovenous malformations of the brain - Al-Shahi Salman, Rustam; Mast, Henning; Stapf, Christian (Whitehouse Publishing, 2007)
Unruptured, asymptomatic arteriovenous malformations (AVMs) lurk in the brains of approximately one person in every thousand; their prevalence, based on four studies of magnetic resonance imaging (MRI) of 7,359 people without brain disorders, 1-4 was 0.1 % (95% confidence interval [CI] 0% to 0.2%). Some of these brain AVMs may be discovered if and when they cause intracranial haemorrhage, epileptic seizure(s), headache, or a focal neurological deficit, but many brain AVMs may potentially lie dormant from the cradle to the grave.